Quantitative Verification of Newton's Gravity and Einstein's Equivalence Principle - Liu, Zirui (Transactions on Computer Science and Intelligent Systems Research, 2025)
This research will focus on understanding gravity, which governs everything from falling apples to orbiting planets. Newton described gravity as a force that pulls on objects, while Einstein later revealed that gravity is the curvature of space itself. Most experiments proving these theories require advanced laboratory equipment, making it difficult for students to test these revolutionary ideas firsthand. My research addresses this problem by creating a simple method that anyone can use to verify Newton's and Einstein's theories of how gravity works. The experiment has two stages, where the measurement will be different. The first stage is before the free-fall, where the phone will be held still, and the app will show data. The second stage is during the free-fall, where the phone will experience a free-fall while the app and the phone will be screen recording. It will show a data when the phone reaches the maximum velocity. As a result, when the phone is at rest, the acceleration is about 9.8 m s-2, which is exactly what Newton predicted for Earth's gravity. When the phone is in free-fall, the acceleration decreases to nearly zero. This proves Einstein's breakthrough idea that gravity "vanishes" during free-fall.
Keywords: Gravity; Free-fall experiment; Newton and Einstein theories.